Soluble L-selectin concentration in bronchoalveolar lavage fluid obtained from infants who develop chronic lung disease of prematurity. Issue 2 (1st March 1998) - Kotecha, S; Silverman, M; Shaw, R J; Klein, N
Abstract : AIMS: To explore the changes in neutrophil adhesion molecule expression and release into bronchoalveolar lavage fluid (BAL) obtained from infants who developed chronic lung disease (CLD). METHODS: BAL fluid was obtained from 37 infants: 18 (median gestation 26 weeks, birthweight 835 g) who developed CLD, 12 (29 weeks, 1345 g) with respiratory distress syndrome (RDS) and seven control infants (33 weeks, 2190 g). RESULTS: Soluble L-selectin (sL-selectin) in BAL fluid from the CLD and non-CLD groups was similar immediately after birth, but in infants who subsequently developed CLD, sL-selectin remained persistently increased (at day 7: CLD 42.6 vs RDS 6.0 ng/ml, p<0.05; CLD vs controls 1.5 ng/ml; p<0.05). CD11b/CD18 expression on neutrophils obtained by BAL increased with time to reach a maximum at 17 days of age in infants who developed CLD. CONCLUSIONS: These results suggest that leucocyte traffic persists in infants who develop CLD and may have an important part to play in the pathogenesis of CLD.